The Nexus among Family Business, Household Finances and Women Empowerment: Evidence from PDHS 2017-18 - Mubeen, Sadaf; Hye, Qazi Muhammad Adnan; Shahid, Muhammad Hassam; Rehan, Raja (Nurture, 2022)
Purpose: This study intends to determine whether family businesses empower women, encourage their entrepreneurship, and enable them to become fully engaged in activities that generate finances by allowing them to select their own business idea. Methodology: Empowering women is crucial for accelerating economic and financial progress. The question of the economic empowerment of women is of utmost importance to political philosophers, social scientists, and reformers because it is currently thought of as a sine qua non of progress for a nation. This study examines the relationship between women’s financial empowerment, business, and the home using data from the 2017–18 Pakistan Demographic and Health Survey (PDHS). For this, we employed binary logistic regression. Findings: Women who are educated and have a job are more empowered than women who are not employed. Furthermore, economic and financial development cannot occur without the advancement of women. Women should be taught technical knowledge and marketing strategies and empowered to develop their skills to create more sustainable businesses. Contribution to literature: This study contributes to the literature in two ways: First, this study utilized the fertility variable which was not utilized in earlier studies. Second, this study identified the women empowerment factors by using four different indicators.